2017
DOI: 10.1039/c7cp03751a
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle aggregates as a model for primitive cellular assemblies

Abstract: Primitive cell models help to understand the role that compartmentalization plays in origin of life scenarios. Here we present a combined experimental and modeling approach towards the construction of simple model systems for primitive cellular assemblies. Charged lipid vesicles aggregate in the presence of oppositely charged biopolymers, such as nucleic acids or polypeptides. Based on zeta potential measurements, dynamic light scattering and cryo-transmission electron-microscopy, we have characterized the beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 53 publications
3
50
0
Order By: Relevance
“…[96] So far, the focus has been on developing microfluidic technologies for controllably trapping one [28,30,62,76,78] or even two [87] GUVs at a defined location. [96] So far, the focus has been on developing microfluidic technologies for controllably trapping one [28,30,62,76,78] or even two [87] GUVs at a defined location.…”
Section: Perspectives For Microfluidic Handling Of Artificial Cellsmentioning
confidence: 99%
“…[96] So far, the focus has been on developing microfluidic technologies for controllably trapping one [28,30,62,76,78] or even two [87] GUVs at a defined location. [96] So far, the focus has been on developing microfluidic technologies for controllably trapping one [28,30,62,76,78] or even two [87] GUVs at a defined location.…”
Section: Perspectives For Microfluidic Handling Of Artificial Cellsmentioning
confidence: 99%
“…63 This ratio is particularly crucial to control the properties of the lipoplexes and thus their applications: lipid/DNA ratio was reported to influence both the formation of lipoplexes and the release of DNA 64 and gene transfer activity. 65 Many authors have shown that the lipid:polyelectrolyte ratio actually controls the formation of MLWV structures 18,28,31-34 over agglutinated single-wall vesicles, [35][36][37] but in fact it is more likely that a general consensus has not been found, yet, and reality often consists in a mixtures of MLWV and agglutinated vesicles, 38 although many authors do not specify it. One of the reasons that could explain such discrepancy is the parallel influence of several other parameters like the charge density on both the lipid membrane and in the polyelectrolytes, the rigidity of the latter, the bending energy of the lipid membrane, the ionic strength and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Several works propose that the lipid:polyelectrolyte ratio controls the fusion of single-wall vesicles MLWV, 18,28,[31][32][33][34] while others rather observe vesicular agglutination under similar conditions. [35][36][37] In fact, a general consensus has not been found and a multiphasic system including agglutinated vesicles and MLWV are actually observed. 38 The question whether or not MLWV, and PESCs in general, are equilibrium structures and how they are formed is still open, especially when they are prepared under non-equilibrium conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Such assemblies are expected to shed light on the emergence and function of early proto‐tissue systems (or the first multicellular organisms or colonies of cells). Although some reports have focused on the aggregation or biomolecular transfer between collections of GUVs, no work has ever investigated how environmental factors effects such systems. External triggers in the early Earth will have surely been essential in the evolution of protocell behavior.…”
Section: Resultsmentioning
confidence: 99%